The Observation of Blast Disease and Its Effect to Rice Yield Using Existing Assessment Method to Support the Indonesian Agriculture Insurance - I Putu Sudiarta; I Komang Candra Giri Prayoga; I Gede Rai Maya Temaja; Gusti Ngurah Alit Susanta Wirya; Masahiro Shishido; Chiharu Hongo (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
One of the causes for the low productivity of rice in Indonesia is the occurrence of rice blast disease. Blast disease is one of the main diseases of rice plants around the world. Therefore to minimise the risk of the lost yield by blast disease, the Ministry of Agriculture of the Republic of Indonesia has the agriculture insurance program. To support these program, the research about observations of blast disease in a fixed location are needed. The objective this research is to confirm pathogens causing the blast disease in the fields, to determine the development of blast disease and its effect to the rice yield (grain weight and straw weight). The study was conducted in a fixed paddy field at Subak Uma Dalem, Sobangan Village, Mengwi District, Badung Regency, Bali Province from February 2019 to April 2019. The data showed that the disease incidence of rice blast increased every week starting from 1st week (28 DAT) until 10th week (104 ATP). Our study confirmed that the fungus caused the blast disease in the field was Magnaporthe oryzae. The higher incidence of blast disease in the field resulted reduced the rice yield by decreasing both grain and straw weights.